1997
DOI: 10.1136/hrt.78.4.376
|View full text |Cite
|
Sign up to set email alerts
|

Long term ventricular performance after intra-atrial correction of transposition: left ventricular filling is the major limitation

Abstract: Objective-To establish the incidence of systolic and diastolic dysfunction of the right and left ventricle in a large cohort of patients after Mustard or Senning operations and to assess changes in the incidence on long term follow up. Design-Postoperative case-control study using radionuclide ventriculography. Ejection fractions, peak filling rates, rapid filling periods and fractions, slow filling periods and fractions, and atrial contraction periods and fractions were studied. Setting-Tertiary care centre, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 23 publications
4
32
0
5
Order By: Relevance
“…The RV variability in assessing right ventricular function and the lack of a uniform definition restrict comparison. The incidence of RV dysfunction in the long term has been shown to be associated with the complexity of the heart defect, [2][3][4]17], which we confirmed by Lange et al [12] that this dysfunction progressed to moderate dysfunction, but maintaining the functional class II.…”
Section: Other Surgical Proceduressupporting
confidence: 78%
See 1 more Smart Citation
“…The RV variability in assessing right ventricular function and the lack of a uniform definition restrict comparison. The incidence of RV dysfunction in the long term has been shown to be associated with the complexity of the heart defect, [2][3][4]17], which we confirmed by Lange et al [12] that this dysfunction progressed to moderate dysfunction, but maintaining the functional class II.…”
Section: Other Surgical Proceduressupporting
confidence: 78%
“…In 40 consecutive operations, we had one death (hospital mortality = 2.5%); these results are possible to compare to others reported series, with mortality ranging from 2% to 5.4% [7,8,12,17]. Whereas, patients with simple TGA submitted to Senning's operation, resulted in a significant difference in the relative number of complex TGA.…”
Section: Late Follow-upsupporting
confidence: 43%
“…38 The incidence of rhythm disturbances (atrial flutter) was lower in the group of patients after Senning repair, and diastolic function was impaired in the majority of patients after Mustard repair, because abnormal ventricular filling may be due, in part, to flow limitation by the atrial baffle. 39, 40 In the present study the female patients had higher BNP, but the difference was not statistically significant. The data extend previous knowledge that BNP is significantly higher in women.…”
Section: Discussionmentioning
confidence: 42%
“…The incidence of moderate or severe RVD shows a wide variation in the literature from 8% at 12 to 18 years 34,35 to 20% and 18% at 20 and 28 years, 12,17 respectively. Kirjavainen et al 11 found a rapid increase of RVD after 10 years and described the probability of normal right ventricular function to be only 52% and 39% 15 years after the Senning procedure in patients with simple and complex TGA, respectively.…”
Section: Systemic Ventricular Failurementioning
confidence: 99%